Role Of The Leader Towards Organizational Citizen Behaviour (OCB) - Abrori Abrori; Ujang Ali (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Successful organizations need employees who will do more than just their formal duties and they are willing to deliver performance more than the expectations. This positive behavior is known as the Organizational Citizen Behavior, and people who display OCB behavior are called good citizens/employees. To develop OCB behavior, it requires intervention from organizational leaders. The leader is a role model in an organization so that any change must start from the top level (leader). Leaders must be able to become a motor (reformist) for all members of the organization. For analyzing the data, linear regression shows that respondents perceive a positive relationship between the role of the leader and OCB. Therefore, a leader is expected to have behavior in supporting employees in having attitudes that are in accordance with OCB. The significance value also shows that the role of the leader affects OCB behavior. The factor that respondents perceive the highest in the role of the leader is empowerment. This means that respondents expect a leader to be a motivator and always encourage employee development. Meanwhile, the highest perceived factor in the OCB variable is awareness of responsibility for duties and obligations.Keyword:Role of Leader, OCB